Relationship between Duration of Illness and Quality of Life in Hypertension Patients - Topik, Mohamad Ilham; Agil, Hilda Meriyandah; Sari, Ilma Widiya (International Journal of Nursing Information, 2023)
No patient does not have the desire to recover in a short time. Apart from assistance from medical drugs, the patient's quality of life is another determining factor. Hypertensive patients show different quality of life. It cannot be confirmed that patients with more extended illness have a worse quality of life. This study aimed to determine the relationship between the length of illness and the quality of life of hypertensive patients. The research method uses a correlational analytic cross-sectional approach. The research location is Jatikarya Community Health Center, Bekasi, Indonesia. Sample selection used a purposive sampling technique with the criteria of inpatients with a medical diagnosis of hypertension, totaling 33 samples. The research instrument used the DQLCTQ quality of life questionnaire and duration of illness checklist. Analysis was carried out using univariate and bivariate statistics using chi-square. The study results showed that most patients (42.4%) had a prolonged illness category of 1-5 years. The quality of life of the majority of hypertensive patients (51.5%) is in the poor category. The conclusion of the statistical hypothetical test shows a significant relationship between the duration of illness and the quality of life of hypertensive patients. The contribution of this research is to provide evidence of the importance of maintaining the patient's quality of life to speed up the recovery period from the disease.